2020
DOI: 10.1038/s41563-020-0759-8
|View full text |Cite
|
Sign up to set email alerts
|

Complex nanostructures in diamond

Abstract: Complex nanostructures in diamondMeteoritic diamonds formed during bolide impacts on Earth and diamond-related materials synthesized by compressing graphite contain a wide variety of complex nanostructures. This Comment highlights and classifies this structural complexity by a systematic hierarchical approach, and discusses the perspectives on nanostructure and properties engineering of diamond-related materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
84
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 36 publications
3
84
1
Order By: Relevance
“…Figure 2a is a bright eld (BF) STEM image from a sample recovered from 15 GPa and 1200 °C, in which diamond (D) and graphite (G) nanodomains are clearly distinguished. In neighboring diamond and graphite domains, the lattice fringes of the two phases are tilted relative to one another, forming interfaces different from the (113) CD or (111) CD types as previously proposed for meteoritic or laboratory-shocked diamonds based on TEM observations 4,5,11,14,25 . High-resolution HAADF-STEM observations further con rm the tightly bonded graphitic and diamond domains (Fig.…”
Section: Main Textmentioning
confidence: 78%
See 1 more Smart Citation
“…Figure 2a is a bright eld (BF) STEM image from a sample recovered from 15 GPa and 1200 °C, in which diamond (D) and graphite (G) nanodomains are clearly distinguished. In neighboring diamond and graphite domains, the lattice fringes of the two phases are tilted relative to one another, forming interfaces different from the (113) CD or (111) CD types as previously proposed for meteoritic or laboratory-shocked diamonds based on TEM observations 4,5,11,14,25 . High-resolution HAADF-STEM observations further con rm the tightly bonded graphitic and diamond domains (Fig.…”
Section: Main Textmentioning
confidence: 78%
“…The proposed crystal structure gives rise to diffraction peaks resembling those of graphite (with an interlayer spacing of 3.0 Å) and diamond. Although the origin of this hybrid structure and its correlation with the graphite-to-diamond transformation remains unclear 4,5 , the idea of hybrid structure provides an alternative view of the reported "compressed graphite" with a 3.1 Å interlayer spacing 12,[18][19][20][21][22] , and may play an important role in understanding the graphite-todiamond transformation.…”
Section: Main Textmentioning
confidence: 99%
“…[1][2][3] Especially, the application of high-performance bulk graphites (HPBGs) is limited by the intrinsically low mechanical strength and anisotropy of graphite. [1,[4][5][6][7][8][9] Various methods have been investigated to enhance the strength and reduce anisotropy of graphite, including decreasing grain size by reducing the particle size of starting materials and introducing reinforcements and binders. [9][10][11][12][13][14][15][16][17] trunks inspires the microstructural design of HPBGs.…”
mentioning
confidence: 99%
“…The formation of paracrystalline diamond is a result of densely distributed nucleation sites developed in compressed C 60 as well as pronounced second-nearest-neighbor short-range order in amorphous diamond due to strong sp 3 bonding. The discovery of paracrystalline diamond adds a new diamond form to the enriched carbon family [15][16][17] , which exhibits distinguishing physical properties and can be furthered exploited to develop new materials. Furthermore, this work reveals the missing link in the length-scale between amorphous and crystalline states across the structural landscape, which has profound implications for recognizing complex structures arising from amorphous materials.Amorphous solids refer to materials that do not possess long-range periodicity as exhibited in crystals [1][2][3][4][5][6][7][8][9][10][11] .…”
mentioning
confidence: 99%
“…We selected zero-dimensional fullerene (C60) in an fcc crystal to monitor its phase evolution at 30 GPa and a temperature range of 1200-1800 K. The relevance of using C60 as the starting material will be addressed in a later section. Previous investigations have demonstrated that C60 can only transform into disordered sp 2 -sp 3 carbon under hydrostatic pressures (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and high temperatures [23][24][25][26] . Here, at an elevated pressure condition of 30 GPa, the X-ray diffraction patterns (XRD) of the recovered samples synthesized at various temperatures are shown in Fig.…”
mentioning
confidence: 99%